Persepsi Adaptasi Mahasiswa Pelaku Usaha terhadap Perubahan Pasar untuk Menjaga Keberlanjutan Bisnis - Setyawati Setyawati; Rani Ambarwati; Rauly Sijabat (INDO PUBLISHING, 2026)
This study aims to determine how student entrepreneurs perceive market changes in their business environment and how they adapt to maintain business continuity. Economic dynamics, changes in consumer behavior, advances in digital marketing, and crises such as the pandemic impact the market. This study employed a qualitative approach, and the research method was descriptive. While the subjects were students running micro and small businesses, the focus was on how students perceive and adapt to market changes. Data collection was conducted through in-depth interviews, observation, and documentation; data validity was ensured through source triangulation, technical triangulation, and member checking. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that student entrepreneurs are aware of significant market changes and are attempting to adapt by using digital media, modifying products, and becoming more creative and innovative. This research is expected to foster student entrepreneurship and assist universities in supporting student businesses.